2017
DOI: 10.1093/scan/nsx138
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic and self-serving goals modulate behavioral and neural responses in deception

Abstract: People tell lies not only for their own self-interests but sometimes also to help others. Little is known about the ways in which different types of goals modulate behaviors and neural responses in deception. The present study investigated the neural processes associated with spontaneous deception that occurs with altruistic reasons (i.e. the money would be donated to charity), self-serving reasons (i.e. the participant receives all of the money) and mixed goals (i.e. the money would be equally split between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
0
37
0
1
Order By: Relevance
“…It is important that we discuss our findings in light of two very recent cognitive neuroscience studies that also investigated the modulatory roles of social‐related goals on dishonest dicision‐making (Cui et al, ; Yin et al, ). One EEG study used the Coin‐Guessing task (Greene & Paxton, ) and found a higher propensity to be dishonest for self‐serving, compared with for prosocial, benefits (Cui et al, ), while the other fMRI study used the Sender‐Receiver Game (Gneezy, ) and found the opposite behavioral pattern (Yin et al, ). Because we used the same task as Cui et al' () study, and found replicating behavioral pattern with theirs, we attribute the discrepancy between ours and Yin et al' () to the difference in study design.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…It is important that we discuss our findings in light of two very recent cognitive neuroscience studies that also investigated the modulatory roles of social‐related goals on dishonest dicision‐making (Cui et al, ; Yin et al, ). One EEG study used the Coin‐Guessing task (Greene & Paxton, ) and found a higher propensity to be dishonest for self‐serving, compared with for prosocial, benefits (Cui et al, ), while the other fMRI study used the Sender‐Receiver Game (Gneezy, ) and found the opposite behavioral pattern (Yin et al, ). Because we used the same task as Cui et al' () study, and found replicating behavioral pattern with theirs, we attribute the discrepancy between ours and Yin et al' () to the difference in study design.…”
Section: Discussionmentioning
confidence: 86%
“…The study reported a reduction in the N2 component when participants were dishonest for prosocial, compared with self‐serving, benefits. Critically, unlike Yin et al (), Cui et al () found a higher propensity to be dishonest for self‐serving benefits than for prosocial benefits. Because scalp‐recorded EEG used in Cui et al' () study has a poor spatial resolution and may not detect signals from the brain areas that are further away from scalp (e.g., ventromedial prefrontal cortex [vmPFC] and striatum [Str]), the exact brain regions in which activity is modulated by social‐related goals is still unknown.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations